Development and Performance Evaluation of a Smart Upper-Limb Rehabilitation Exercise Device - Bogja Jeoung; Muncheong Choi; Alchan Kim (Sensors, 2024)
User-friendly rehabilitation medical devices can enhance health and the quality of life through the convergence of information communication and medical technology. Muscle contraction enables bodily movement, and the assessment of muscle strength is crucial. Muscle contraction includes isometric, isotonic, and isokinetic types. Many individuals with physical disabilities rely on wheelchairs due to lower-limb paralysis. There is a substantial correlation between the level of upper-limb functional recovery and the quality of daily life. This study aimed to design and evaluate a device that utilizes various muscle contractions to enhance the effectiveness of upper-limb rehabilitation exercises. The results from the isometric performance assessment showed percentage error rates of >30% for 5–30 kg. Correction equations were employed, and the isometric performance assessment resulted in error rates below 2.1% for 5–30 kg. Isokinetic performance assessment using video analysis evaluated a consistent wire speed from 10 cm/s to 70 cm/s with an average error rate of 0.91% across all speeds. This study demonstrates the ability to accurately measure various muscle contractions and showcases the potential for real-time feedback. This highlights how such a device could be helpful for target groups, including older adults and individuals with disabilities, during upper-limb rehabilitation exercises.